FUNGSI KONSUMSI RUMAH TANGGA DI INDONESIA (PENDEKATAN MODEL KOREKSI KESALAHAN) - Maryam Sangaji (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2009)
Keynesian theory about consumption states that household consumption (C) relatedpositively with present income: the greater income the more consumption. Besidethat, interest rate influence negatively toward household consumption, because ifthe interest rate is low then the loan cost also low, so the factor encourage householdto increase it consumption. The results showed that income level related positivelywith household consumption level. While the interest rate related negatively withconsumption level. It means that the greater income encourage the household toincrease its consumption. But the increase is not as high as the income level. Thenthe higher interest rate will cause the household increase its saving, so decrease theconsumption. The test by using error correction model (ECM) showed that balancevariable of ECT is significant, where for that the household consumption adaptedwith the income level change and the interest rate at the same period.Keywords: Household Consumption Level, Income, Interest Rate, and ErrorCorrection Model.